2002
DOI: 10.1038/sj.npp.1300103
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Haloperidol Downregulates Dopamine Synthesis Capacity in the Brain of Schizophrenic Patients In Vivo

Abstract: The antipsychotic effect of neuroleptics cannot be attributed entirely to acute blockade of postsynaptic D 2 -like dopamine (DA) receptors, but may arise in conjunction with the delayed depolarization block of the presynaptic neurons and reduced DA synthesis capacity. Whereas the phenomenon of depolarization block is well established in animals, it is unknown if a similar phenomenon occurs in humans treated with neuroleptics. We hypothesized that haloperidol treatment should result in decreased DA synthesis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 60 publications
(59 reference statements)
2
54
2
1
Order By: Relevance
“…Eight male patients with diagnosis of schizophrenia (Diagnostic and Statistical Manual of Mental Disorders,Ed 4;age,37.3 Ϯ 6.3 years) and 15 male healthy volunteers (mean Ϯ SD age, 37.3 Ϯ 6.4 years) were selected from cohorts in previously published FDOPA/PET studies; in the present reanalysis of subjects from the original group of nine unmedicated patients with schizophrenia (Gründer et al, 2003), a single patient was excluded as a result of uncorrectable head motion during the later PET scanning period (60 -120 min), i.e., in the interval that had been excluded from the previous non-steady-state analysis. The present control subjects were selected from several previously published cohorts of normal subjects (Gründer et al, 2003;Heinz et al, 2005;Vernaleken et al, 2006) so as to obtain an age composition identical to that of the eight patients. All subjects had provided written informed consent for the previous studies, which had been approved by the Research and Ethics Committee of the University of Mainz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight male patients with diagnosis of schizophrenia (Diagnostic and Statistical Manual of Mental Disorders,Ed 4;age,37.3 Ϯ 6.3 years) and 15 male healthy volunteers (mean Ϯ SD age, 37.3 Ϯ 6.4 years) were selected from cohorts in previously published FDOPA/PET studies; in the present reanalysis of subjects from the original group of nine unmedicated patients with schizophrenia (Gründer et al, 2003), a single patient was excluded as a result of uncorrectable head motion during the later PET scanning period (60 -120 min), i.e., in the interval that had been excluded from the previous non-steady-state analysis. The present control subjects were selected from several previously published cohorts of normal subjects (Gründer et al, 2003;Heinz et al, 2005;Vernaleken et al, 2006) so as to obtain an age composition identical to that of the eight patients. All subjects had provided written informed consent for the previous studies, which had been approved by the Research and Ethics Committee of the University of Mainz.…”
Section: Methodsmentioning
confidence: 99%
“…Three patients were entirely drug-naive, whereas the remainder had been treated previously with various doses of oral neuroleptics, with pause of medication to the PET session. Trained raters assessed psychopathological symptoms on the day of the PET scan (Gründer et al, 2003). The mean positive and negative syndrome scale (PANSS) was 80.1 Ϯ 4.7, of which the positive score was 15.4 Ϯ 3.5 and the negative score was 23.6 Ϯ 4.0.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the allocation of subjects to each of these three groups was nonrandomized, but based on the medication prescribed by the in-charge clinician at the time of MRI scan. According to the existing literature on brain changes following administration of antipsychotics (Chakos et al, 1994;Cohen et al, 2003;Christensen et al, 2004;Grunder et al, 2003;Honey et al, 1999;Huang et al, 1999;Miller et al, 1997aMiller et al, , b, 2001Wotanis et al, 2003), the mean length of treatment of 8 weeks of our sample would be sufficient to observe brain changes in association with antipsychotic use.…”
Section: Pharmacological Treatmentmentioning
confidence: 97%
“…Furthermore, in vivo imaging studies of schizophrenia have provided evidence that the right-left asymmetry of the dopamine (DA) synthesis capacity and of the dopamine transporter (DAT) binding in the caudate are both lost in antipsychotic-naive patients (Hietala et al, 1999(Hietala et al, , 1995Hsiao et al, 2003;Laakso et al, 2000). In addition, neuroleptics are able to change the balance of hemispheric activity, thus improving left-hemispheric attentional processes (for a review, see Gruzelier, 1999), and a recent study demonstrated that haloperidol-induced downregulation of DA synthesis was significantly greater in the left than in the right striatum (Grunder et al, 2003). Finally, a highly significant correlation was reported between depressive symptoms in antipsychotic-naive schizophrenia and DA synthesis capacity in the left striatum (Hietala et al, 1999).…”
Section: Introductionmentioning
confidence: 99%